PERANCANGAN BUKU ILUSTRASI JEJAK KULINER KHAS KAWANUA SEBAGAI MEDIA INFORMASI - Gloria Rumondor; Yana Erlyana (Prahasta Publisher (manage by: DRPM Institut Bisnis dan Teknologi Indonesia), 2022)
Indonesia is known as a country that has cultural diversity. This is an asset for Indonesia, especially in the tourism sector in utilizing local culture as an attraction for tourists. One of them is the use of local culinary culture. As for the design of this thesis, it raises the superior culinary culture of the city of Manado, a city known for its cuisine that is rich in spices. The use of illustrations in the book can give its own emotional impression to the readers, this statement is supported by an online questionnaire that has been randomly distributed to 110 respondents. This book is intended for teenagers aged 18-25 years to increase their knowledge of other regional cultures in Indonesia. With this research, it is hoped that the awareness to maintain Indonesian culture is an important thing for teenagers aged 18-25 years to increase.